Vulnerable suspects in police interviews: Exploring current practice in England and Wales. Issue 1 (18th November 2019) - Farrugia, Laura; Gabbert, Fiona
Abstract: Mentally disordered individuals are increasingly coming into contact with the police. The current study explored investigative interview practice with mentally disordered suspects to examine how they respond and the impact this has on the level of information obtained. Transcripts of interviews conducted with vulnerable and nonvulnerable suspects ( N = 66) were analysed using a specially designed coding framework. Results highlighted that best practice is generally not being adhered to regarding questioning techniques (for example, the use of open questions). Furthermore, although police officers altered their communication to suit the needs of the vulnerable suspect, they were also more likely to use minimisation tactics. Mentally disordered suspects sought more clarification for open questions and provided more information to closed questions. They also demonstrated higher levels of vulnerability (suggestibility and compliance) when compared with their nonvulnerable counterparts. Implications regarding interviewing methods for this vulnerable group are discussed.